Pengaruh Edukasi terhadap Tingkat Pengetahuan Penggunaan Antibiotik pada Pasien Rawat Jalan di Puskesmas Perawatan Buli: The Effect of Education on The Level of Knowledge of Antibiotic Use in Outpatients at Buli Health Care Center - Primania Maria Puren; Khusna, Khotimatul; Risma Sakti Pambudi (Indonesian Journal of Pharmacy and Natural Product, 2025)
Antibiotics are drugs which has a function to kill bacteria. Antibiotics are ethical drugs that are often used in pharmacological therapy. Low levels of knowledge regarding the use of antibiotics can result in irrational use, thereby risking antibiotic side effects. Providing education is one way that can be used to increase knowledge about antibiotics in patients. The aim of this study was to determine the effect of providing education on the level of knowledge of outpatients about antibiotics at the Buli Health Care Center. This research method is quasi experimental using a one group pre and post-test design and data collection from a perspective using purposive sampling technique for 96 respondents. The research results showed that 57.3% (55 respondents) obtained antibiotics without a doctor's prescription and 42.7% (41 respondents) obtained a doctor's prescription. During the pre-test, 22.9% (22 respondents) were in the poor category, 41.7% (40 respondents) in the sufficient category, 35.4% (34 respondents) in the good category. In the post-test 20.8% (20 respondents) were in the fair category, 32.3% (31 respondents) in the good category, 46.9% (45 respondents) in the very good category. The results obtained were tested using the Wilcoxon signed rank which shows the difference in scores between before and after being given education with a significant value of 0.00 (p value <0.05). The conclusion of this study is that there is an influence of education on the level of knowledge of outpatients at the Buli Care Community Health Center.   ABSTRAK Antibiotik adalah obat yang berfungsi membunuh bakteri. Antibiotik termasuk dalam golongan obat keras yang sering digunakan pada tatalaksana terapi farmakologi. Rendahnya tingkat pengetahuan mengenai penggunaan antibiotik dapat mengakibatkan penggunaan yang tidak rasional, sehingga berisiko menimbulkan efek samping antibiotik. Pemberian edukasi adalah salah satu cara yang bisa digunakan untuk meningkatkan pengetahuan tentang antibiotik pada pasien. Tujuan penelitian ini untuk mengetahui pengaruh pemberian edukasi terhadap tingkat pengetahuan pasien rawat jalan tentang antibiotik di Puskesmas Perawatan Buli. Metode penelitian ini adalah quasi experimental menggunakan desain one group pre and post-test dan pengambilan data secara perspektif dengan tekhnik purposive sampling kepada 96 responden. Hasil penelitian didapatkan antibiotik diperoleh tanpa resep dokter 57,3% (55 responden) dan dengan resep dokter 42,7% (41 responden). Saat pre-test 22,9% (22 responden) kategori kurang, 41,7% (40 responden) kategori cukup, 35,4% (34 responden) kategori baik. Pada post-test 20,8% (20 responden) kategori cukup, 32,3% (31 responden) kategori baik, 46,9% (45 responden) kategori sangat baik. Hasil yang diperoleh diuji menggunakan Wilcoxon signed rank yang menunjukkan perbedaan skor antara sebelum dan sesudah diberikan edukasi dengan nilai signifikan 0,00 (pvalue<0,05). Kesimpulan pada penelitian ini adalah terdapat pengaruh edukasi terhadap tingkat pengetahuan pasien rawat jalan di Puskesmas Perawatan Buli.